FORMULASI DAN UJI EFEKTIVITAS KELEMBABAN SEDIAAN KRIM M/A EKSTRAK KULIT MANGGIS (Garcinia mangostana L.) - Clarista, Helaria Eren; Ulfa, Ade Maria; Nofita, Nofita (JURNAL PENELITIAN TERAPAN KESEHATAN, 2024)
Skin can be said to be moist if it has a water content of 40%. One way to maintain the effectiveness of moisture in the skin is by using moisturizing cosmetics, such as cream. Mangosteen fruit (Garcinia mangostana L.) is a plant that has benefits, especially in its skin. There are compounds that have been proven to provide a moisturizing effect thereby protecting the skin from skin oxidation and free radicals. The purpose of making this cream is to moisturize the skin and utilize mangosteen peel extract. The advantage of cream with the O/W emulsion type is that it does not cause a sticky feeling, is easy to spread on the skin surface, is soft, and is easily washed off with water. Mangosteen peel extract was obtained using the maceration method with 96% ethanol. The cream preparation was made into 4 formulations K0, F1, F2, and F3 based on the amount of mangosteen extract used. Then a Physical Evaluation Test, Irritation Test, Likeability Test and Moisture Test were carried out. Each formulation was tested for moisture using an SK-8 skin analyzer. Evaluation of cream use was carried out by 12 volunteers for 5 days with use during the day. The overall results obtained were that the 3% mangosteen extract F1 formulation met the quality standards for physical cream preparations and had a high increase in water content in the volunteers' skin with a percent water content value of 50.16%. Meanwhile, in the analysis of the Wilcoxon test and Paired T-test data, a significance value of 0.00 (<0.05) was obtained which means that mangosteen peel extract cream can increase moisture in the skin, and variations in extract concentration have an influence on the effectiveness of the cream in moisturizing the skin.